Answer:
mAE
It's too short. Write at least 20 characters to explain it well.
Answer:
Simplifying
x2 + -4y2 = 25
Solving
x2 + -4y2 = 25
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add '4y2' to each side of the equation.
x2 + -4y2 + 4y2 = 25 + 4y2
Combine like terms: -4y2 + 4y2 = 0
x2 + 0 = 25 + 4y2
x2 = 25 + 4y2
Simplifying
x2 = 25 + 4y2
Reorder the terms:
-25 + x2 + -4y2 = 25 + 4y2 + -25 + -4y2
Reorder the terms:
-25 + x2 + -4y2 = 25 + -25 + 4y2 + -4y2
Combine like terms: 25 + -25 = 0
-25 + x2 + -4y2 = 0 + 4y2 + -4y2
-25 + x2 + -4y2 = 4y2 + -4y2
Combine like terms: 4y2 + -4y2 = 0
-25 + x2 + -4y2 = 0
The solution to this equation could not be determined.
Step-by-step sorry if im wrong
When you write it as an inequality you get x + 19 ≈ 8.2 and when you solve it it should look like x + 19 ≈ 8.2
19 ≈ - <u>19
</u> x ≈ -10.8<u>
</u>
60/150 = 40%
Hope this helps :D
Answer:
25
Step-by-step explanation:
Expression: <em>(2⁸ ⋅ 5⁻⁵ ⋅ 19⁰)⁻² ⋅ (5⁻²/2³)⁴ ⋅ 2²⁸</em>
Inner-most powers: 2⁻¹⁶ • 5¹⁰ • 1 • 5⁻⁸/2¹² • 2²⁸
Combine like terms: 2¹² • 5²/2¹²
Cancel out: 5²
Solve: 25